Modified Electroconvulsive Therapy in a Patient with Gastric Adenocarcinoma and Metastases to Bone and Liver - Gennie Wang; Brian Milne; Rachel Rooney; Tarit Saha (Case Reports in Psychiatry)
Background. In addition to general anesthesia, muscle relaxants are given prior to electroconvulsive therapy (ECT) in order to prevent musculoskeletal injury. Higher doses of muscle relaxants have been suggested for patients at high risk for bone fractures; however, there are adverse side effects associated with these higher doses. Aims. We present a successful case of ECT to treat chronic major depressive disorder in a 62-year-old woman at high risk of bone fracture due to gastric adenocarcinoma with metastases to bone and liver. Case. Increasing doses of the muscle relaxant succinylcholine (0.45–0.74 mg/kg) were sufficient to prevent musculoskeletal complications throughout the course of 9 bifrontal ECT treatments. Following treatment, the patient reported and demonstrated markedly improved mood and functionality, enabling her transfer to a palliative care facility. Conclusion. Standard doses of succinylcholine were sufficient to mitigate the risk of pathological fractures in this patient with metastatic bone lesions. As there are established risks to using high doses of succinylcholine, with no evidence that higher doses reduce the incidence of fractures in high-risk populations, we suggest taking a conservative approach, using clinical observation and periodic plain radiography to dictate succinylcholine dose titration in such high-risk patients.